The Labour Market of Artists. Free, But Not Wild - Ilczuk , Dorota; Karpińska, Anna (Edukacja Ekonomistów i Menedżerów, 2018)
The authors present a summary of previous research projects in the field of professional situation of artists in Poland. They refer to the conducted research of the Labour Market of Artists and Creators in Poland as well as the expertise of “The Support for Artists and Creators. International Perspective”. They also present their vision of a support system for creators and artists, which comprises: the monitoring and analysis; the status of an artist; remuneration (government programmes and potential mechanisms to stimulate demand; taxes; copyright law); insurance; foreign promotion of artists; the organisation of the labour market of artists and adjusting education to its requirements. Finally, they refer to the presentation delivered at the conference “Creative Economy in Poland, Facts and Myths”, organised by the Creative Economy Research Center of SWPS University. The main postulate proposed by the authors is to create a platform for constant monitoring and analysis of the professional situation of artists in Poland, to which the project of estimating the number of artists, creators and performers should lead.